2018
DOI: 10.1038/s41598-018-21385-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Strength-Ductility Enhancement of a Nano-Lamellar AlCoCrFeNi2.1 Eutectic High Entropy Alloy by Cryo-Rolling and Annealing

Abstract: Nano-lamellar (L12 + B2) AlCoCrFeNi2.1 eutectic high entropy alloy (EHEA) was processed by cryo-rolling and annealing. The EHEA developed a novel hierarchical microstructure featured by fine lamellar regions consisting of FCC lamellae filled with ultrafine FCC grains (average size ~200–250 nm) and B2 lamellae, and coarse non-lamellar regions consisting of ultrafine FCC (average size ~200–250 nm), few coarse recrystallized FCC grains and rather coarse unrecrystallized B2 phase (~2.5 µm). This complex and hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(72 citation statements)
references
References 57 publications
3
69
0
Order By: Relevance
“…4) demonstrates that the nonhomogeneous plastic deformation in the HGS imparts an additional long-range hardening effect from unusually high back stresses. After this example, several HEAs/MEAs have also been shown to exhibit wide hysteresis loops 36,39,45,59 (see Fig. 4).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…4) demonstrates that the nonhomogeneous plastic deformation in the HGS imparts an additional long-range hardening effect from unusually high back stresses. After this example, several HEAs/MEAs have also been shown to exhibit wide hysteresis loops 36,39,45,59 (see Fig. 4).…”
mentioning
confidence: 93%
“…3). Another multiphase heterogeneity design is the dual-phase eutectic lamella (DPEL) HEA 36,[43][44][45][46] . One example is a eutectic HEA, which in addition to the FCC phase contains a second BCC phase as well as Crenriched nanoprecipitates 44 .…”
mentioning
confidence: 99%
“…In other words, it should be straightforward to achieve good combinations of strength and ductility by introducing heterogeneous structures. For instance, a heterostructured multi-phase AlCoCrFeNi 2.1 HEA shows a simultaneous strength-ductility enhancement in comparison with its homogenous counterpart [24]. More recently, it has been reported that a single-phase fcc CrNiCo mediumentropy alloy (MEA), which is derived from the concept of HEA, with a heterogeneous grain structure exhibits superior mechanical properties [25].…”
mentioning
confidence: 99%
“…An abundance of investigations have emerged in the literature focusing on microstructural characteristics, defect evolution as well as mechanical properties for HEAs after SPD. [99][100][101][102][103][104][105][106][107][108][109] A recent work by Bhattacharjee et al 106 reported that the nanolamellar AlCoCrFeNi 2.1 HEA, which was achieved by cryorolling and annealing processes, exhibited a remarkable increase in both the yield strength and the ultimate tensile strength (UTS) without sacrificing too much ductility [ Fig. 8(a)].…”
Section: Grain Coarseningmentioning
confidence: 99%